Effectiveness and meaningful use of paediatric surgical safety checklists and their implementation strategies: a systematic review with narrative synthesis. Issue 10 (16th October 2017) - Lagoo, Janaka; Lopushinsky, Steven R; Haynes, Alex B; Bain, Paul; Flageole, Helene; Skarsgard, Erik D; Brindle, Mary E
Abstract : Objective: To examine the effectiveness and meaningful use of paediatric surgical safety checklists (SSCs) and their implementation strategies through a systematic review with narrative synthesis. Summary background data: Since the launch of the WHO SSC, checklists have been integrated into surgical systems worldwide. Information is sparse on how SSCs have been integrated into the paediatric surgical environment. Methods: A broad search strategy was created using Pubmed, Embase, CINAHL, Cochrane Central, Web of Science, Science Citation Index and Conference Proceedings Citation Index. Abstracts and full texts were screened independently, in duplicate for inclusion. Extracted study characteristic and outcomes generated themes explored through subgroup analyses and idea webbing. Results: 1826 of 1921 studies were excluded after title and abstract review (kappa 0.77) and 47 after full-text review (kappa 0.86). 20 studies were of sufficient quality for narrative synthesis. Clinical outcomes were not affected by SSC introduction in studies without implementation strategies. A comprehensive SSC implementation strategy in developing countries demonstrated improved outcomes in high-risk surgeries. Narrative synthesis suggests that meaningful compliance is inconsistently measured and rarely achieved. Strategies involving feedback improved compliance. Stakeholder-developed implementation strategies, including team-based education, achieved greater acceptance. Three studies suggest that parental involvement in the SSC is valued by parents, nurses and physicians and may improve patient safety. Conclusions: A SSC implementation strategy focused on paediatric patients and their families can achieve high acceptability and good compliance. SSCs' role in improving measures of paediatric surgical outcome is not well established, but they may be effective when used within a comprehensive implementation strategy especially for high-risk patients in low-resource settings.